Error of measurement of the diameter of the stem of Guazuma crinita with forceps, metric belt and diametric belt, Ucayali, Peruvian Amazon - Galván Gildemeiste, Octavio Francisco Javier (2022)
Increased commercial plantations of Guazuma crinita, a prominent species in the Peruvian Amazon, require improved tree measurements for wood volume quantification. The objective of this research was to determine the error in the measurement of the normal diameter of the stem (dbh) and in the calculation of the volume, when the normal diameter of the stem is measured with a tape measure, a diameter tape and an aluminum caliper. Forty-one trees from a 13-year-old Guazuma crinita forest plantation were measured in the Pucallpa area, Peruvian Amazon. Two diameters were measured with the caliper and the averages were obtained with the arithmetic mean and the geometric mean. The irregularity of the cross section of the stems of the trees was close to one. The descriptive and inferential analysis found that the measurement of a dbh, with a caliper, differs markedly from the other methods and generates the largest relative error, with 4% for the normal diameter and 7.9% for the volume, at the tree level. But, at the hectare level, an absolute error of up to 7.7 m3/ha was found, an important quantity from the industrial and financial dimension. It was concluded that the normal diameter can be measured, indifferently, with a tape measure, diametric tape or through the average of two diameters with an aluminum caliper. In addition, it was concluded that it is indistinct to use the arithmetic mean or the geometric mean.